FAKTOR PENENTU KINERJA MANAJERIAL (Studi pada Pemerintah Daerah Kupang) - Selfi Samadara (Ekonomi Syariah IAIN Kudus, 2016)
Tujuan dari kajian ini: 1) untuk mengkaji pengaruh budgetary goal characteristics pada job-relevant information, 2) untuk mengkaji pengaruh budgetary goal characteristics pada kinerja manajerial, 3) untuk meneliti pengaruh job-relevant information pada kinerja manajerial, 4) pengaruh budgetary goal characteristics pada kinerja manajerial melalui job-relevant information sebagai variabel intervening. Sampel terdiri dari 78 pejabat struktural di kabupaten/kota Kupang. Artikel ini berlaku analisis path menggunakan tes t untuk menguji hipotesis. Hasil pengujian hipotesis pertama menunjukkan bahwa kesan partisipasi anggaran (X1), evaluasi anggaran (X4) pada job-relevant information (X6) secara langsung adalah signifikan. Hasil pengujian hipotesis kedua menunjukkan bahwa kejelasan target anggaran (X2), anggaran umpan balik (X3), dan kesulitan dalam target anggaran (X5) memiliki akibat langsung terhadap performa Manajerial (Y). Hipotesis ketiga hasil pengujian yang menunjukkan bahwa job-relevant information yang relevan (X6) memiliki pengaruh langsung terhadap kinerja Manajerial (Y). Hasil pengujian hipotesis keempat menunjukkan bahwa job-relevant information adalah variabel perantaraan antara partisipasi anggaran (x1) dan evaluasi anggaran (x4) terhadap kinerja manajerial (Y).Kata Kunci: Budgetary Goal Characteristics, Job-Relevant Information, Kinerja Managerial THE DETERMINING FACTORS OF MANAGERIAL PERFORMACE (STUDY ON REGIONAL GOVERNMENT OF KUPANG)Abstract The purpose of this study are: 1) to examine the effect of budgetary goal characteristics on job-relevant information, 2) to examine the effect of budgetary goal characteristics on managerial performance, 3) to examine the effect of job-relevant information on managerial performance, 4) to examine the effect of budgetary goal characteristics on managerial performance through job-relevant information as an intervening variable. The sample consists of 78 Head of Department of Kupang. This article applies path analysis using the t test to test the hypothesis. The result of testing the first hypothesis suggests that the effect of budget participation (X1), evaluation of the budget (X4) on the Job relevant information (X6) directly is significant. The result of testing the second hypothesis suggests that the Clarity of the budget target (X2), Feedback budget (X3), and the Difficulty of budget target (X5) have a direct effect toward Managerial Performance (Y). The third hypothesis-testing result shows that job-relevant information (X6) has direct influences toward Managerial Performance (Y). The fourth hypothesis testing result indicates that Job relevant information is an intervening variable between budgetary participation (X1) and evaluation of the budget (X4) toward managerial performance (Y).Keywords: Budgetary Goal Charateristics, Job-Relevant Information, Kinerja Manajerial